Named entity annotation of an 18th-century transcribed corpus: problems and challenges - Cameron, Helena (2022)
This paper reviews a stage of the process of annotating named entities in 18th-century texts to enrich historical research sources and link them to other bases. The categories in question are person, location and organisation, valid categories for historian analysis. We discuss the difficulties observed in the process and point eventual solutions.